2019
DOI: 10.1186/s13195-019-0490-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to fluoride aggravates the impairment in learning and memory and neuropathological lesions in mice carrying the APP/PS1 double-transgenic mutation

Abstract: Background: Alzheimer's disease (AD) is responsible for 60-70% of all cases of dementia. On the other hand, the tap water consumed by hundreds of millions of people has been fluoridated to prevent tooth decay. However, little is known about the influence of fluoride on the expression of APP and subsequent changes in learning and memory and neuropathological injury. Our aim here was to determine whether exposure to fluoride aggravates the neuropathological lesions in mice carrying the amyloid precursor protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 65 publications
(70 reference statements)
0
18
0
Order By: Relevance
“…In previous studies, it has been demonstrated that APP/PS1 mice showed cognitive decline in terms of spatial learning and memory [ 30 , 38 , 39 ]. Therefore, we evaluated whether DXI was able to rescue the cognitive impairment observed in this mice model through both tests, MWM and NORT.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it has been demonstrated that APP/PS1 mice showed cognitive decline in terms of spatial learning and memory [ 30 , 38 , 39 ]. Therefore, we evaluated whether DXI was able to rescue the cognitive impairment observed in this mice model through both tests, MWM and NORT.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it has been demonstrated that APP/PS1 mice showed cognitive decline in terms of spatial learning and memory (30,38,39). Therefore, we evaluated whether DXI was able to rescue the cognitive impairment observed in this mice model through both tests, MWM and NORT.…”
Section: Treatment Improves Cognitive Decline Observed In Both App/ps1 Mice Fed With Conventional Chow and Obesogenic Dietmentioning
confidence: 94%
“…Each mouse was forced to find a submerged escape platform in a circular pool filled with water (25-26° C) rendered opaque with powdered milk [50]. During the familiarization session and acquisition phase (four trials/day for four consecutive days), the mouse was given as long as 60 s to find the hidden platform and then allowed to remain seated on this platform for 5 s, after which the animal was returned to its home cage.…”
Section: The Morris Water Maze (Mwm) Test Of Spatial Learning and Memorymentioning
confidence: 99%
“…The level of Aβ42 in mouse brains was determined utilizing an Amyloid β42 Mouse ELISA kit in accordance with the manufacturer's protocol [50]. In brief, after homogenization and centrifugation of the tissue, the pellets obtained were extracted with 5 M guanidine-HCl.…”
Section: Determination Of Aβ42 By Elisamentioning
confidence: 99%